SAT0389 Comparison of ankylosing spondylitis and non-radiographic axial spondyloarthritis in a multi-ethnic asian population of singapore. (15th June 2017) - Hong, C; Kwan, YH; Fong, W
Abstract : Background: The relationship between non-radiographic axial spondyloarthritis (nr-axSpA) and ankylosing spondylitis (AS) is currently debated. Till date, there is no study exploring the differences between AS and nr-axSpA in Asia. Objectives: The primary objective of this study was to compare clinical characteristics, disease activity, patient-reported outcomes and associated co-morbidities between patients with AS and nr-axSpA in a multiethnic Asian population of Singapore. Methods: All patients fulfilled 2009 ASAS classification criteria for axial SpA. Of these, all AS patients fulfilled the modified New York criteria. AS and nr-axSpA patients were retrieved from the PREcision medicine in SPONdyloarthritis for Better Outcomes and Disease Remission (PRESPOND) registry in Singapore General Hospital. Patients were followed up over 2 years. Baseline characteristics, medications, disease activity, patient-reported outcomes and inflammatory markers prior and 6 months post treatment were recorded using standardized questionnaires. Results: 262 AxSpA patients (82% Chinese, 79% males) were included. Current mean age (S.D.) was 41.7 (13.7) years, mean age of diagnosis was 31.7 (12.5) years, mean length of disease was 10.1 (8.3) years and body mass index was 24.7 (6.3) kg/m 2, which was similar between AS and nr-axSpA patients. AS patients were older [mean age 42.7 (13.5) vs 37.4 (13.8) years, p=0.02], had longer disease duration [mean disease duration 10.9 (8.7) vs 6.4 (4.8) years, p<0.01], more frequently HLA-B27 positive (82% vs 68%, p=0.03), associated with uveitis (33% vs 17%, p=0.03), and hypertensive (17% vs 0%, p<0.01) compared to nr-AxSpA respectively. nr-axSpA patients had higher BASDAI [mean BASDAI 4.2 (1.6) vs 3.5 (1.9), p=0.02], BAS-G [mean BAS-G 4.7 (1.7) vs 3.9 (2.1), p<0.01] and ASQOL [mean ASQOL 4.9 (4.8) vs 3.5 (4.1), p=0.04] scores compared to AS patients respectively at baseline. Peripheral arthritis, enthesitis, dactylitis, psoriasis, inflammatory bowel disease, hyperlipidemia, cardiac disease, diabetes mellitus, patient global assessment, BASFI, HAQ and SF-36 physical component summary and mental component summary were similar in both groups at baseline. Mean BASDAI, BAS-G, patient global assessment, HAQ and SF-36 physical component summary and mental component summary scores were similar at 12 months between both groups, except for BASFI, which was higher in AS patients (p<0.001). Medications used were similar between AS and nr-AxSpA patients (81% of axial SpA patients were on NSAIDs, 31% on concomitant DMARDs and 14% on biologics). Mean erythrocyte sedimentation rate and C-reactive protein were similar between both groups at baseline and 12 months post treatment. Conclusions: In our multi-ethnic Asian cohort, patients with AS are more likely to be HLA-B27 positive, have uveitis, hypertension, and poorer physical function despite therapy; whilst nr-axSpA patients have higher baseline disease activity scores and tend to experience poorer well-being and quality of life. Although both groups represent different aspects of the same disease, they respond similarly to treatment. Disclosure of Interest: None declared